Overview of Adolescent Mental Health - Antu, Mihrawaty S.; Latinapa, Yusril D; Katili, Ansar (An Idea Health Journal, 2025)
Mental health shows self-ability in managing feeling anf overcoming difficulties in daily life. Factors causing mental disorder during teenager life are exposure to difficulties, stress of self adjustment with friends of the same age, exploration of identity. This study aimed at investigating an overview of teenager's mental health at SMP N 3 Kabila, Bone Bolango Regency. This study applied descriptive method. Population were all students of SMP N 3 Kabila amunted to 127. Samples were determined using simple random sampling, hence, it obtained 96 respondents. Technique of data collection was strenght and difficulties questionnaires (SDQ). Findings revealed that most of the students had normal mental health and only some of students had borderline mental health. It is expected to school party to be able to maintaim students who have normal health and to help those who have borderline mental health